PERANCANGAN BALAI MULTI-ETNIK SEBAGAI WADAH UNTUK MEMPERSATUKAN KEMBALI ETNIS DAYAK DAN MADURA DI KAMPUNG PELADIS - Brigita Pricillia; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2022)
Indonesia is a very diverse country, from that diversity there are various ethnic. However, the negative side, is the diversity and differences that can later lead to ethnic conflicts. Just like what happened in Borneo since 1950-2001, where conflicts between Dayak and Madurese ethnic groups repeatedly occurred. Kampung Peladis, which is located in West Borneo, is one proof that there are still borders and boundaries between Dayak and Madurese ethnic groups. Starting from the pattern of settlements, to the daily activities of inter-ethnic groups, and less mingling with each other. Therefore, with the aim of reuniting the two ethnic groups, through rethinking the typology as a design strategy, Rituals of Re-Unite settings so that the two ethnic groups will inevitably meet and communicate with each other at the Multi-Ethnic Hall in Kampung Peladis. Bloomfield once said, reconciliation means finding a way to live side by side with former opponents, to love and forgive them. They need to manage impressions because they